Cytotoxicity of red fruit ethyl acetate extract (Pandanus conoideus lam.) on squamous cell carcinoma cell line (HSC-3) - Dicha Yuliadewi Rahmawati; Wita Anggraini; Melanie S Djamil (Wolters Kluwer Medknow Publications, 2021)
Background: Oral squamous carcinoma is a malignancy of the head-and-neck area that comprises 90% of all oral cancers. Research continues to look for therapies with low concentrations of cytotoxicity to reduce morbidity in patients with tongue carcinoma. The red fruit plant (Pandanus conoideus Lam.) is believed to have anticancer activity because of its antiproliferation activity. The high antioxidant content in red fruit is able to ward off and break free radicals that carry carcinogen compounds. Red fruit ethyl acetate extract has the highest antioxidant activity compared with other fractions, such as water, chloroform, methanol, and n-hexane. Objective: This study sought to evaluate whether red fruit ethyl acetate extract is able to inhibit the growth of the Human Squamous Carcinoma (HSC-3) cell line with varying concentration levels and exposure times. Method: The HSC-3 cell line was treated with extract concentrations of 10 μg/mL, 20 μg/mL, and 40 μg/mL and exposure times of 6 and 12 h. Doxorubicin was used as a positive control, and dimethyl sulfoxide was used as a negative control. The percentage of viable HSC-3 cells was calculated through the 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide assay cytotoxicity test. All groups were statistically compared, and P < 0.05 was considered to be a statistically significant difference. Result: A concentration of 20 μg/mL with an exposure time of 6 h and a concentration of 10 μg/mL with an exposure time of 12 h showed a significant difference compared with the positive control of doxorubicin (P < 0.05). Conclusion: The results showed that the higher the concentration of red fruit ethyl acetate extract, the lower the percentage of viable HSC-3 cells.